2022
DOI: 10.48550/arxiv.2204.11906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clogging, Diode and Collective Effects of Skyrmions in Funnel Geometries

Abstract: Using a particle-based model, we examine the collective dynamics of skyrmions interacting with a funnel potential under dc driving as the skyrmion density and relative strength of the Magnus and damping terms are varied. For driving in the easy direction, we find that increasing the skyrmion density reduces the average skyrmion velocity due to jamming of skyrmions near the funnel opening, while the Magnus force causes skyrmions to accumulate on one side of the funnel array. For driving in the hard direction, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, skyrmions could be destroyed by touching the edge. Recently, it has been shown that a more effective strategy to confine, protect, and control skyrmions in magnetic thin films is to construct defect lines with different magnetic properties [63][64][65][66][67][68][69][70][71][72][73][74] , which can be realized in engineered multilayer nanostructures 75) or by using focused irradiation 76) . However, the helicity dynamics of a frustrated skyrmion confined by defect lines have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, skyrmions could be destroyed by touching the edge. Recently, it has been shown that a more effective strategy to confine, protect, and control skyrmions in magnetic thin films is to construct defect lines with different magnetic properties [63][64][65][66][67][68][69][70][71][72][73][74] , which can be realized in engineered multilayer nanostructures 75) or by using focused irradiation 76) . However, the helicity dynamics of a frustrated skyrmion confined by defect lines have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In magnetic systems, funnel obstacles or pinning barriers may also affect the dynamics of particle-like skyrmions driven by external forces. For example, the dynamics of a single skyrmion or multiple skyrmions can be effectively modified using an array of funnel barriers [39,40], which could lead to the clogging, diode, and collective effects of skyrmions. However, there are still many open questions in the complex dynamics of multiple skyrmions interacting with funnel obstacles.…”
Section: Introductionmentioning
confidence: 99%